Assessing the role of Environmental Legislation in Mitigating Climate Risk in GCC: A quantile ARDL approach - Mohamed Sami Ben Ali (23073832) (2025)
Climate risk manifested through rising temperatures, extreme weather events, and ecological degradation poses a growing threat to environmental and economic stability, particularly in resource-dependent regions such as the Gulf Cooperation Council (GCC). This paper aims to empirically examine the short- and long-term effects of environmental legislation on climate risk, considering the roles of eco-friendly regulations, Information and Communication Technology (ICT), and domestic extraction in the GCC countries. Using the panel Quantile ARDL technique, the findings suggest that climate legislation effectively mitigates climate risk. This effect is notably increased at the upper quantile in the long run. A similar effect of ICT indicates its vital role in managing climate risk. On the contrary, GDP significantly exacerbates climate risk, especially at lower and median quantiles in the short term. The results demonstrate the uni-directional effect of climate legislation and ICT on climate risk, illustrating the effectiveness of ICT and regulatory measures in addressing climate challenges. These findings underscore the significance of the legislative framework in mitigating climate risk, underscoring the need for new policy interventions to address climate vulnerability. Other Information Published in: Economic Analysis and Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eap.2025.10.007